Correlating Interictal Spikes with Sigma and Delta Dynamics during Non-Rapid-Eye-Movement-Sleep - Zubler, Frédéric; Rubino, Annalisa; Lo Russo, Giorgio; Schindler, Kaspar; Nobili, Lino (Frontiers in Neurology, 2017)
Interictal spikes (IS) are one of the major hallmarks of epilepsy. Understanding the factors promoting or suppressing IS would increase our comprehension of epilepsy, and possibly open new avenues for therapy. Sleep strongly influences epileptic activity, and the modulatory effects of the different sleep stages on IS have been studied for decades. However, several aspects are still disputed, in particular the role of sleep spindles and slow waves in the activation of IS during Non-REM sleep. Here we correlate the rate of IS with quantitative measures derived from Stereo-EEG during one Non-REM cycle in 10 patients suffering from drug-resistant epilepsy due to type 2 focal cortical dysplasia. We show that the IS rate is positively correlated with sigma power (a surrogate for sleep-spindle density), but negatively correlated with delta power (surrogate for slow wave activity). In addition, we present two new indices for quantifying the spatial and temporal instability of sleep. We found that both instability indices are correlated with a high IS rate. The main contribution of this study is to confirm the suppressive effect of stable deep sleep on interictal spikes. This result might influence future guidelines for therapy of patients suffering from epilepsy and sleep disorders